Assessing Audience Members' Ability to Identify the Media Source of a Health Campaign Disseminated via Different Media - Pettigrew, Simone; Jongenelis, Michelle; Phillips, Fiona; Slevin, Terry; Allom, Vanessa; Keightley, Stacey; Beasley, Sarah (Frontiers in Public Health, 2018)
Background: An important criterion for health campaign media selection is the ability to achieve campaign awareness among target audiences. However, existing campaign exposure metrics cannot be applied across both traditional and digital media, which complicates decision making. The present study assessed the validity of using self-report as a measure of the extent to which different types of media achieve campaign awareness to assist in determining appropriate media budget allocations. Methods: A quasi-experiment involving varying combinations of television, online video, and online display smoking cessation advertisements was conducted to determine whether audience members were able to accurately report the source of their exposure to the campaign. Results: Of the 719 Western Australian adults sampled (50% males, 50 females, 50% smokers, 50% non-smokers), 64% reported seeing the campaign in the previous two weeks. Of these, 91% reported seeing the advertisement on television, 8% on online video, and 21% on online display (respondents could select multiple media). Despite proportional scheduling of the three media over the discrete campaign periods, in most cases respondents assumed their exposure had occurred via television, regardless of the actual source of exposure. Conclusions: Among both smokers and non-smokers, television had primacy in memory regardless of the actual media used. As such, relying on self-reported recall is unlikely to constitute a reliable method of assessing target audience exposure to campaigns on different media where those media are all screen-based. The results highlight the need for alternative media effectiveness metrics that permit direct comparisons between traditional and digital media.